Documenting a contested memory: Symbols in the changing city space of Cairo. (June 2017) - Awad, Sarah H
This article looks at how symbols in the urban environment are intentionally produced and modified to regulate a community's collective memory. Our urban environment is filled with symbols in the form of images, text, and structures that embody certain narratives about the past. Once those symbols are introduced into the city space they take a life span of their own in a continuous process of reproduction and reconstruction by different social actors. In the context of the city space of Cairo in the five years following the 2011 Egyptian revolution, I will look on the one side at efforts of activists to preserve the memory of the revolution through graffiti murals and the utilization of public space, and from the other, the authority's efforts to replace those initiatives with its own official narrative. Building on the concept of collective memory, as well as Bartlett's studies of serial reproductions and theorization of reconstructive remembering, I will follow the reproduction of different symbols in the city and how they were perceived and remembered by pedestrians.